2004
DOI: 10.2136/sssaj2004.2069
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Gradients and Topsoil Additions Affect Soil Properties of Virginia Created Wetlands

Abstract: and retain nutrients (Mitsch and Gosselink, 2000). Without suitable soil properties, CWs may never functionally As the role of soil properties in the development of created wetreplace the natural wetlands that were destroyed. lands (CWs) has not received adequate attention in regulatory or scientific communities, this study was conducted to evaluate the devel-As soils of natural wetlands have been exposed to opment of soil properties in 11 CWs in Virginia ranging from 4 to 16 wetland processes for periods of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…A lower stock variability by level was observed in the Alocrisols-Neoluvisols compared with the Colluviosols-Fluviosols (Fig. 3) and confirmed the high spatial variability of soil properties in these locations [12,23,30,41].…”
Section: Effects Of Soil Type and Hydromorphysupporting
confidence: 69%
“…A lower stock variability by level was observed in the Alocrisols-Neoluvisols compared with the Colluviosols-Fluviosols (Fig. 3) and confirmed the high spatial variability of soil properties in these locations [12,23,30,41].…”
Section: Effects Of Soil Type and Hydromorphysupporting
confidence: 69%
“…Many studies have advocated for the amendment of created wetlands with OM in the form of salvaged topsoil or compost to help them achieve reference functionality (Stauffer and Brooks 1997;Whittecar and Daniels 1999;Bruland and Richardson 2004). Indeed, studies have found that moderate loading of compost OM into a created wetland increase woody plant development (Bailey et al 2007) and soil functions, such as microbial decomposition and increased denitrification enzyme activity (Bruland and Richardson 2009;Sutton-Grier et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Site history is complex, with one unsuccessful restoration attempt for this formerly forested wetland being followed by an experimental addition of organic matter amendments to improve tree growth. For more detail on site characteristics, see Bruland and Richardson (2004), Bergschneider (2005), and Bailey et al (2007).…”
Section: Methodsmentioning
confidence: 99%